Pengelolaan Penyaluran Bantuan Rumah Layak Huni (RLH) pada Masa Pandemi Covid-19 di Kota Pekanbaru Provinsi Riau - Puspita , Alisa; Nasution, Mimin Sundari (Journal of Economics, Bussiness and Management Issues, 2023)
The aim of this research is to determine management and the influencing factors. Qualitative research method with data sources namely primary and secondary data, data collection techniques based on observation, interviews, documentation and analysis. The result of the author’s research are that the management of distribution of livable housing assistance during the Covid-19 pandemic in Pekanbaru City, Riau Province is still not effective. The lack of innovation and quick solutions in distribution management during the Covid-19 pandemic has made distribution management less effective. There are still many deficiencies found, such as in providing socialization and registration for recipients of livable housing, assistance, it still uses a manual system and has obstacles, namely changes in distribution targets, distribution procedures that are not yet effective and the management of infrastructure is not in accordance with the budget provided, due to the impact due to the Covid-19 outbreak, the budget allocated was cut to handle Covid-19, but in the field the facilities avaulable to recipients of livable housing assistance were incomplet.